Perempuan Peran Ganda : Perspektif Teori Pertukaran Perilaku Dan Teori Pertukaran Sosial - Lina Warniati (JAROW: Journal of Ar-Raniry on Social Work, 2024)
Women having careers does not mean competing with men or forcing gender equality so they can be fully equal to men. Progress over time has brought very rapid changes in human life, both in the fields of technology and science. Along with progress in economic development, higher demands are placed on each individual in these changes. Women's dual roles are not an achievement that is easy for women to achieve. Qualitative descriptive methods are used in this research. A scientific research to dig deeper into a social problem which is the aim of the author. The focus of this research aims to find out how women have multiple roles from the perspective of behavioral exchange theory. social in women's dual role in career and household, where women must balance the demands they face. The role played must be able to do work outside the home, be able to manage the household, be a wife, and a mother who will take care of her family. It can be concluded that women have a dual role in the exchange of social behavior because it focuses on individual behavior in social relationships and social interactions. Women's work is the process of consuming physical and mental energy for someone who is paid to work as a housewife and teacher, a PT Sawit factory worker. So, the role of women in the family is the mother as a character shaper for the child and the child's partner in education for the welfare of their life. From the perspective of social behavioral exchange, women can be considered as active participants in determining their multiple roles.